2017
DOI: 10.1556/066.2017.46.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-chain inulin and modified starch on the physicochemical and rheological properties of doogh (Iranian yogurt drink)

Abstract: In this research, simultaneous contribution of long-chain inulin (0-2.34%) and modifi ed starch (0-0.58%) on the physical stability and rheological properties of doogh within 30 days of production was studied. Increased concentration of both hydrocolloids redounded to improvements in physical stability, apparent viscosity, fl ow behaviour, and viscoelastic properties compared to the control sample. Fitting the data to Herschel-Bulkley model showed a decrease in fl ow behaviour index, while consistency coeffi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…The relationship between shear rate and apparent viscosity is nonlinear, so, Doogh is a non-Newtonian fluid. It seems that pseudo-plastic behavior of control and treated samples in the presence of hydrocolloids could be due to the high amount of dry matter and the increased internal interaction between the particles in Doogh (Karim et al, 2017). The results related to the rheological behavior were similar to other studies when hydrocolloids were used in acidic milk beverages (Khanniri et al, 2019).…”
Section: Viscosity and Rheological Propertiessupporting
confidence: 82%
See 1 more Smart Citation
“…The relationship between shear rate and apparent viscosity is nonlinear, so, Doogh is a non-Newtonian fluid. It seems that pseudo-plastic behavior of control and treated samples in the presence of hydrocolloids could be due to the high amount of dry matter and the increased internal interaction between the particles in Doogh (Karim et al, 2017). The results related to the rheological behavior were similar to other studies when hydrocolloids were used in acidic milk beverages (Khanniri et al, 2019).…”
Section: Viscosity and Rheological Propertiessupporting
confidence: 82%
“…Nowadays, Doogh is produced as a fermented dairy product in Iran, both traditionally and industrially, as a standard product (Zarei et al, 2015). This fermented product is produced and consumed worldwide, such as yogurt drink in Europe, Kefir and Kumis in the Middle East, Ayran in Turkey, Lassi in India and Doogh in Iran (Karim et al, 2017). Doogh is usually consumed because of desirable sensory properties, high digestibility, microbiological and nutritional quality.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the relationship between the independent variables (konjac‐mannan, xanthan, and tragacanth compositions) and responses (Ketchup characteristics), experimental results were statistically analyzed through the MINITAB software (release 17) where error probability value of p < .05 is considered “significant.” Simultaneous comparison of multiple sets of observations were, respectively, followed by parametric analysis of variance (ANOVA) and nonparametric Kruskal–Wallis in the case of normal and abnormal data series distribution to investigate the differences detected at 0.05% level of probability. Tukey's pair‐wise comparison was also applied to study the significance of average sample results (Golchoobi, Alimi, Shokoohi, & Yousefi, ; Karim, Alimi, Shokoohi, & Fazeli, ). This method, in fact, detects which pairs differed among others comparing every pairs of means.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 revealed that with increasing the amount of GTD and PKP at a constant shear rate, the apparent viscosity is increased. It seems that the presence of hydrocolloids and dietary fiber, increases internal interaction between the particles in Doogh samples (Karim et al, 2017). These rheological results were similar to other studies when hydrocolloids were used in acidic milk beverages (Khanniri et al, 2019; Hashemi, Gharibzahedi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…During the fermentation process various types of beneficial nutrient compounds such as essential amino acids, organic acids, antibiotics, and bacteriocins are produced by lactic acid bacteria (Afzali et al, 2020). Similar Doogh products are consumed in other countries with different names such as yogurt drink in Europe, Kefir and Kumis in the Middle East, Ayran in Turkey, and Lassi in India (Karim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%